A formação do professor pesquisador na produção científica dos encontros nacionais de didática e prática de ensino: 1994-2000 - Silvana Ventorim (2005)
Its goal is the debate investigation about researcher professor formation in scientific production in the Encontros Nacionais de Didática e Prática de Ensino (1994- 2000), aiming at learning and systemizing concepts, reasons, hypotheses and implications from which research relation, professor formation and pedagogical practice is formed. The knowledge catalogue about researcher professor formation taken from ENDIPEs is complemented with relations between its academic production and its emergent perspective of science. It is taken by presupposition that ENDIPEs reflect, promote and provoke the debate about researcher professor formation movement, what makes certain the professor formation mediated by research. It is orientated by the bibliographic documental research that recognizes political and epistemological status of the documents, because they establish the relation between discourses and practices in the educational area. The sources used were printed and electronic documents (books and annals). The 77 works of VII, VIII, IX and X ENDIPEs analyses revealed that scientific production considers research professor formation in a political and epistemological dimension that suggests a new meaning for the professor role a new invention of power and knowledge ways. Through internal works development, it is confirmed the idea that researcher professor movement was formed by ENDIPEs, which knowledge, subjects, objects, theories, practices and institutions are integrated with research and teaching. It indicates the accomplishment of researches in formation and professor practice as a possibility for a formation and a qualitative teaching practice, raising power to professional development, to practice improvement and to knowledge production about teaching, what has implicated complementary research identities. It is shown the necessity of a different relation with the knowledge and its production process, based on variety and opening knowledge, thinking again about certainties and indicating other logics and new explanations in communication and professional commitment, what demands the doubt and questioning exercise, aiming a processual and conception of knowledge The research identity understanding in professor formation and in practice, that implicates investigation and intervention has as principle to go deep into concepts as knowledge and intervention, professor and researcher role, theory and practice and knowledge production. It is considered that investigative process by/ with professors shows the review necessities, above all in the research itself, in the knowledge production process and in social relation researchers and professors. The discussion about concept, the role and the importance of the research is indicated as fundamental. By and in ENDIPEs, the study object of this thesis progressed and became stronger, incorporating into doing the formation and practice of the professor, as a movement built, progressing and becoming stronger ENDIPEs themselves as an area of expression of vast experiences in the scientific educational area.